2020
DOI: 10.1177/1471301220909246
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of south Asian carers into a survey-based research study

Abstract: Because of challenges involved in recruitment, little research has focused on care needs of minority ethnic groups. This article reports on a study that recruited 186 British south Asian carers of people with dementia. Four obstacles were faced: language barriers, confusion over research, feelings of shame/stigma, and mistrust. Researchers drew on various methods: enlisting multilingual researchers; activating contacts in minority ethnic communities; engaging with community groups; emphasising potential for en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In addition to the strategies outlined in the review, other studies have highlighted that the patient– physician relationship is a key factor in recruiting ethnic minorities ( Anjorin and Lipsky 2018 ; Fry et al 2021 ). Literature suggests that patients learn about clinical trials through their physician, and so sociocultural differences between the patient and the physician can exacerbate challenges to participation (e.g., understanding the study aims and the potential benefit/ harm) ( Anjorin and Lipsky 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the strategies outlined in the review, other studies have highlighted that the patient– physician relationship is a key factor in recruiting ethnic minorities ( Anjorin and Lipsky 2018 ; Fry et al 2021 ). Literature suggests that patients learn about clinical trials through their physician, and so sociocultural differences between the patient and the physician can exacerbate challenges to participation (e.g., understanding the study aims and the potential benefit/ harm) ( Anjorin and Lipsky 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Literature suggests that patients learn about clinical trials through their physician, and so sociocultural differences between the patient and the physician can exacerbate challenges to participation (e.g., understanding the study aims and the potential benefit/ harm) ( Anjorin and Lipsky 2018 ). Overcoming these challenges with the encouragement of constructive relationships may lead to positive outcomes towards recruiting minority patients into clinical trials ( Fry et al 2021 ). Literature also suggests that that having a lead researcher from the same ethnic background as the participant may also improve ethnic minority participation in research ( Fry et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…include more flexibility in interview completion such as via telephone as well as engaging caregivers in understanding the value and usefulness of research. A recent study involving South Asian caregivers of patients with Dementia also reported that factors such as confusion over research and mistrust are significant obstacles to participation [53]. We progressed with exploratory analyses nonetheless as there is no data on the diagnostic accuracy of adapted screening questionnaires with the South Asian HD patient population.…”
Section: Plos Onementioning
confidence: 99%